Case Report: “Gourd-Shaped” Heart Strangled by Localized Annular Calcification of the Left Ventricle: A Rare Case of Constrictive Pericarditis - Yang, Zhiyun; Wang, Hui; Lv, Qiang; Du, Xin; Zhu, Junming; Dong, Jianzeng (Frontiers in Cardiovascular Medicine, 2022)
We report a rare case of a 43-year-old woman with calcific annular constrictive pericarditis (CP) encircling the basal segment of the right ventricle and the mid-segment of the left ventricle (LV) lateral wall. Over time, localized calcification has caused LV to be tightly strangled and shaped like a gourd. However, multimodality imaging confirmed no significantly clinical constriction associated with decreased cardiac movement and function. Additionally, cardiac magnetic resonance feature tracking confirmed the relatively preserved diastolic function and the characteristic ‘plateau’ pattern of CP. The treatment strategy of this case is challenging and dialectical.